The effects of easy and difficult business relationship evaluations on purchase intentions - Camou Viacava, Juan José; Baptista, Paulo de Paula (Review of Business Management, 2020)
Purpose – This research aims to investigate the different impacts of easy (fluency) and difficult (disfluency) business relationship evaluations on future purchase intentions. In addition, it seeks to investigate the mediating role of confidence in these evaluations and present a new form of fluency manipulation performed directly by satisfaction evaluations. Design/methodology/approach – This research includes a first experiment with a 3 (fluency: easy vs difficult vs control) x 2 (hypothetical scenario of satisfaction vs dissatisfaction) factorial design, using 180 undergraduate students, and a second single factor experiment (fluency: easy vs difficult vs control) with 326 consumers evaluating their financial services provider. Both used a between-subject design with the individuals being randomly distributed between the scenarios. Findings – Dissatisfied consumers who perceived ease in evaluating commercial relationships have increased confidence in these evaluations, negatively influencing their purchase intentions. Meanwhile, satisfied consumers are generally overconfident, being equally affected by perceived difficulty or ease due to a direct bias from the evaluation, which increases purchase intentions. Originality/value – The results demonstrate that fluency (perceived ease or difficulty) depends on the valence of the evaluations, directly affecting (positive valence) or indirectly affecting (negative valence) subsequent decisions. We also present a new, faster, and more practical way to manipulate fluency. Furthermore, we raise some ethical questions as these effects result in biased decisions.